Simulasi Pemodelan Sebaran Suhu Akibat Limbah Air Panas Power Plant PT. Amman Mineral Nusa Tenggara di Teluk Benete, Sumbawa Barat - Rexcha Oktavania Sukmawanty; Kunarso Kunarso; Lilik Maslukah; Aris Ismanto (Jurnal Kelautan, 2022)
ABSTRACTPower Plant PT. Amman Mineral Nusa Tenggara is a thermal power station (PLTU) that supplies electricity located in West Sumbawa Regency. The power plant utilizes seawater from Benete Bay as cooling water for the condenser, which produces hot water waste (heat) that released back into the water. The hot water waste that generated must pass the cooling stage so the temperature of the hot water waste can close to the normal temperature of the water. The objective of this research is to determine the temperature distribution due to hot water waste released by the power plant and predict the temperature distribution in the event of a cooling system failure. To carry out the study used several data include temperature, currents, bathymetry, tides, and the discharge of heat water. The research method used is advection-dispersion hydrodynamic modeling by Delft3D software. The results of hydrodynamic modelling showed that the distribution of hot water waste in normal conditions and in the cooling system where there is a damage, are leading to the east and west according to the direction of tidal current. Result of measurement to the water around the outlet shows the average temperature in the water coloumn is 28,5oC. The temperature increase due to hot water waste reaches 2,5oC in normal conditions, and 3,5oC in conditions if there is damage to the cooling system. In normal conditions, the dispersion area of hot water waste is 25,39 Ha during spring tide, and 9,31 Ha during neap tide. In the damaged condition of cooling system, the dispersion area during spring tide is 41,95 Ha and 35,61 Ha during neap tide.Keywords: Distribution, Waste Heat, Temperature, Delft3DABSTRAKPower Plant PT. Amman Mineral Nusa Tenggara yang terletak di Kabupaten Sumbawa Barat merupakan PLTU yang mensuplai kebutuhan listrik untuk operasional perusahaan. Power plant memanfaatkan air laut dari Teluk Benete sebagai media pendingin untuk kondensor yang hasil akhirnya berupa limbah air panas (bahang) yang dikeluarkan kembali ke perairan. Limbah air panas yang akan dikeluarkan harus melewati tahap pendinginan sehingga suhu limbah air panas dapat mendekati suhu normal perairan. Penelitian ini bertujuan untuk mengetahui sebaran suhu akibat limbah air panas yang dikeluarkan oleh power plant dan memprediksi sebaran suhu apabila terjadi kerusakan sistem pendingin. Data primer yang digunakan dalam penelitian ini adalah data temperatur dan arus laut. Sedangkan data sekunder yang digunakan adalah data batimetri, pasang surut, dan debit limbah air bahang. Metode yang digunakan dalam penelitian ini adalah pemodelan hidrodinamika adveksi-dispersi dengan software Delft3D. Hasil penelitian menunjukkan sebaran limbah air panas pada kondisi normal maupun apabila terjadi kerusakan sistem pendingin mengarah ke arah timur dan barat, sesuai dengan arah pergerakan arus. Kenaikan suhu akibat limbah air bahang mencapai 2,5oC pada kondisi normal, dan 3,5oC pada kondisi apabila terjadi kerusakan sistem pendingin dari suhu rata- rata perairan sebesar 28,5 oC. Pada kondisi normal, luas sebaran pada saat pasang purnama sebesar 25,39 Ha dan pada saat pasang perbani sebesar 9,31 Ha, sedangkan pada kondisi apabila terjadi kerusakan sistem pendingin luas sebaran limbah saat pasang purnama sebesar 41,95 Ha dan ketika pasang perbani sebesar 35,61 Ha.Kata Kunci: Sebaran, Limbah Air Panas, Temperatur, Delft3D